Evaluating the evaluator: private providers' views of a quality assurance agency. Issue 2 (4th May 2019) - Tamrat, Wondwosen
ABSTRACT: The Higher Education Relevance and Quality Agency (HERQA) was established in Ethiopia to spearhead efforts in the assurance of quality at a national level. This study examined the views of private providers about the operational features and practices of HERQA. Findings revealed that despite its significant contributions in formalising and popularising a nationally designed quality assurance régime, private providers consider HERQA to be deficient as regards its capacity, resources, autonomy, communication, double standard practices and internal and external evaluation systems. Based on the findings, it is suggested that HERQA needs to mitigate its structural and operational deficiencies and boost its capacities if it seeks to respond favourably to the mounting challenges of the fledgling and fast-growing higher education system in Ethiopia.